2010
DOI: 10.5194/hess-14-911-2010
|View full text |Cite
|
Sign up to set email alerts
|

Towards automatic calibration of 2-D flood propagation models

Abstract: Abstract. Hydraulic models for flood propagation description are an essential tool in many fields and are used, for example, for flood hazard and risk assessments, evaluation of flood control measures, etc. Nowadays there are many models of different complexity regarding the mathematical foundation and spatial dimensions available, and most of them are comparatively easy to operate due to sophisticated tools for model setup and control. However, the calibration of these models is still underdeveloped in contra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…The ranges are comparable to those published in hydraulic text books and other publications (Chow et al, 1988;Werner et al, 2005;Pappenberger et al, 2007b;Fabio et al, 2010). The ranges chosen enclose the values typically expected for the flow conditions, but are also large enough in order to enable compensation of model errors -most likely geometric errors -by the calibration.…”
Section: Parameter Classificationsupporting
confidence: 64%
See 1 more Smart Citation
“…The ranges are comparable to those published in hydraulic text books and other publications (Chow et al, 1988;Werner et al, 2005;Pappenberger et al, 2007b;Fabio et al, 2010). The ranges chosen enclose the values typically expected for the flow conditions, but are also large enough in order to enable compensation of model errors -most likely geometric errors -by the calibration.…”
Section: Parameter Classificationsupporting
confidence: 64%
“…Automatic calibration adjusts parameters automatically according to a specified search scheme optimising numerical measures of goodness of fit of the model results to the data. Automatic calibration gained increasing popularity in the past decades, because it alleviates the chief drawbacks of manual approaches which are subjective, tedious, much dependent on the expertise of modellers, and need huge amount of labour (Duan et al, 1993;Madsen, 2000;Fabio et al, 2010). A lot of research has been carried out for developing automated calibration routines or applying them to a large number of water-related applications (Duan et al, 1992;Solomatine et al, 1999;Skahill and Doherty, 2006;Bárdossy and Singh, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the river roughness coefficient was the most important and sensitive parameter. River roughness was represented in the model as Manning coefficients, which we initially estimated based on published values corresponding to particular types of rivers and canals (Chow, 1959;Fabio et al, 2010;Dung et al, 2011). First, referring to Chow (1959), we set the Manning coefficients as 0.020 (irrigation channel, straight, on hard-packed smooth sand), 0.025 (earth channel excavated in alluvial silt soil, with deposits of sand on the bottom and grass growth), and 0.033 (natural channel, somewhat irregular side slopes, very little variation in cross section).…”
Section: Model Setup and Data Preparationmentioning
confidence: 99%
“…For example, Fabio et al . () used 390 flood depths points to calibrate a comparatively simple 2D flood propagation model. The equifinality of the parameter sets showed that the model structure is not sufficient to properly describe the information content of the calibration data.…”
Section: Lessons Learnedmentioning
confidence: 99%